GDP revisions are not cool: The impact of statistical agencies' trade-off - Stylianos Asimakopoulos; Magdalena Lalik; Joan Paredes; José Salvado García (European Central Bank (ECB), 2023)
Official estimates of economic growth are regularly revised and therefore forecasts for GDP growth are done on the basis of ever-changing data. The economic literature has intensively studied the properties of those revisions and their implications for forecasting models. However, it is much less known about the reasons for Statistical Agencies (SAs) to revise their estimates. In order to be timely and reliable, SAs have an explicit interest in not revising their initial GDP estimates too much, while they are much more open to revise GDP components over time. More than a curiosity, we exploit this resulting cross-correlation of GDP components revisions to build a model to better forecast GDP.
Keywords: C01; C82; E01; 330; revisions; real-time data; news and noise